“Radical TAs”: Co-creating liberatory classrooms with undergraduate students - Schaefer, Mattie; Henson, Tenaja; Wells, Rehshetta; Ezell, Sarena; Holton, Judia; Pitre, Donzahniya; Craven, Krista (International Journal for Students as Partners, 2022)
In this paper, we suggest that when undergraduate students are engaged as full teaching partners with professors in the college classroom, more liberatory and transformative educational spaces can be created. This paper is based on findings from a qualitative participatory study led by a team of six undergraduate students and one professor who engaged in a series of collaborative teaching endeavors (known as the Radical Teaching Assistant Project) at a small liberal arts college in the southern United States. Our findings suggest that positioning undergraduate students as co-teachers in college classrooms (a) fosters deeper student engagement through relatability, (b) creates more accessible and generative learning environments, (c) subverts knowledge hierarchies in the academy, (d) challenges dominant discourses and norms in the classroom, and (e) provides a space to engage in prefigurative politics. We also discuss some key challenges that arise through this model of collaborative teaching. Our findings suggest that students have much to offer college classrooms when they are central actors in designing course curricula and facilitating class sessions for their peers.